Computerized electrocardiography in American pit bull terrier dogs - Cardoso, Mauro José Lahm (2013)
Electrocardiography (ECG) is an essential examination for evaluation of patient with heart disease is great importance the diagnosis of arrhythmias. The examination can determine source f rhythm and frequency depolarization heart, providing information in clinical status myocardium, since deflections P-QRS-T tracing can be altered by disease or physiological factor. With advancement of computer technology, computerized electrocardiography has been used in human medicine as auxiliary diagnostic method and currently is being increasingly used in veterinary medicine. The objectives this study were to study e computerized electrocardiographic parameters in dogs breed American Pit Bull Terrier, comparing them with patterns species. In present study, we evaluated electrocardiographic examinations 42 dogs the breed American Pit Bull clinically healthy, 22 males and 20 females, aged between 1 and 6 years. Sinus rhythm was observed in 57% of dogs showed sinus rhythm and only 26% were wandering pacemaker. The electrocardiographic values obtained from these dogs computerized ECG were within the normal range of species, except the duration of the P wave which had longer than 0.04 seconds in 24% of dogs. We conclude that the dogs of the breed American Pit Bull Terrier have the same electrocardiographic values obtained in other breeds by the computerized method, except for the increase in P-wave duration.